Analysis of phonon transport through heterointerfaces of InGaN/GaN via Raman imaging using double-laser system: The effect of crystal defects at heterointerface. (1st November 2022) - Nakayama, Tomoya; Ito, Kotaro; Ma, Bei; Iida, Daisuke; Najmi, Mohammed A.; Ohkawa, Kazuhiro; Ishitani, Yoshihiro
Abstract: The pump and probe technique in Raman spectroscopy is used to demonstrate the phonon transport properties of an In0.05 Ga0.95 N/GaN heterostructure. The pump laser generates phonons via the energy relaxation of the generated carriers in the electronic energy bands of the InGaN layer, and the Raman signal is obtained using the probe laser. In the present study, 532-nm and 325-nm lasers are utilized. The phonon transport from the InGaN layer to the GaN layer across the heterointerface is blocked near the crystal defects inherited from the GaN layer. This phenomenon is consistent with our previous report demonstrating the blocking of phonon transport across the In0.16 Ga0.84 N/GaN heterointerface near the misfit dislocations in the In0.16 Ga0.84 N layer. Lateral phonon transport over a distance of 20 μm is observed, which is dominated by diffusive phonon transport. This method has the advantage of enabling the study of phonon transport processes inside and at interfaces of films with crystal defects by visualizing the shift of phonon-mode energies due to local heating.